Step * 1 2 of Lemma rsum-telescopes


1. : ℤ
2. {n...}
3. {n..m 1-} ⟶ ℝ
4. {n..m 1-} ⟶ ℝ
5. ∀i:{n..m-}. (y[i 1] x[i])
6. ∀d:ℕ((d ≤ (m n))  {x[k] y[k] n≤k≤d} (x[n d] y[n])))
⊢ Σ{x[k] y[k] n≤k≤m} (x[m] y[n])
BY
(InstHyp [⌜n⌝(-1)⋅ THEN Auto) }


Latex:


Latex:

1.  n  :  \mBbbZ{}
2.  m  :  \{n...\}
3.  x  :  \{n..m  +  1\msupminus{}\}  {}\mrightarrow{}  \mBbbR{}
4.  y  :  \{n..m  +  1\msupminus{}\}  {}\mrightarrow{}  \mBbbR{}
5.  \mforall{}i:\{n..m\msupminus{}\}.  (y[i  +  1]  =  x[i])
6.  \mforall{}d:\mBbbN{}.  ((d  \mleq{}  (m  -  n))  {}\mRightarrow{}  (\mSigma{}\{x[k]  -  y[k]  |  n\mleq{}k\mleq{}n  +  d\}  =  (x[n  +  d]  -  y[n])))
\mvdash{}  \mSigma{}\{x[k]  -  y[k]  |  n\mleq{}k\mleq{}m\}  =  (x[m]  -  y[n])


By


Latex:
(InstHyp  [\mkleeneopen{}m  -  n\mkleeneclose{}]  (-1)\mcdot{}  THEN  Auto)




Home Index